Composition of the body in male patients with rheumatoid arthritis with account of androgenic status - A. A. Kondrashov; N. A. Shostak (Научно-практическая ревматология)
Aim. To evaluate alterations in body composition and bone mineral density (BMD) in male patients with rheumatoid arthritis (RA) taking into account their androgen status. Materials and methods. The single-stage study included 96 male RA patients. The mean age of patients was 59 [54; 64.75] years. The control group included 30 healthy men of comparable age. The androgen status assessment was based on sex hormone binding globulin (SHBG), total and free testosterone levels determination. Body composition and BMD measurements were performed using dual-energy X-ray absorptiometry (DXA) on the Stratos dR device (DMS, France) with the program “Whole Body”. Depending on the combination of BMD, lean- and fat-mass parameters, phenotypes of body composition were determined. The study was approved by Pirogov Russian National Research Medical University Local Ethics Committee. All patients signed informed consent.Results. Generally, lumbar spine, femoral neck and total hip BMD in RA patients was significantly less than in the control group (p<0.05). In 69 (71.9%) patients with RA osteopenic syndrome was detected. It was represented by osteopenia and osteoporosis (OP) in 60.4% and 11.5% of cases respectively. The spine and femoral neck BMD correlated negatively with SHBG level, and positive correlation was detected between BMD and free testosterone level. The RA patients had significantly less lean mass than the control group. Low lean mass was found in 48.9% of patients in the main group and was not detected in the control group. Appendicular lean mass (ALM) correlated positively with total and free testosterone levels. According to DXA data, the adipose tissue content (%) corresponded to obesity in 63.3% of patients. Adipose tissue indicators correlated negatively with SHBG, total and free testosterone levels. The BMD of various skeleton parts correlated positively with trunk lean mass, and the femoral neck and total hip BMD had positive relationships with body mass index (BMI). Body composition alterations were revealed in 93.2% of RA patients. The most common phenotypes were osteosarcopenic obesity (25%), osteopenic obesity (21.6%) and osteopenic sarcopenia (14.8%). Conclusion. Our study shows that RA course in men is associated with the development of osteopenic syndrome in 71.9% of cases and ALM decrease to diagnostic values of sarcopenia in 48.9% of cases. This fact should be considered in the development of a gender approach to RA patients management and rehabilitation.